Antioxidative Potency of Dolphin Serum Albumin Is Stronger Than That of Human Serum Albumin Irrespective of Substitution of 34Cysteine With Serine - Suzuki, Miwa; Anraku, Makoto; Hakamata, Wataru; Kishida, Takushi; Ueda, Keiichi; Endoh, Tomoko (Frontiers in Physiology, 2020)
Serum albumin (SA), the most abundant protein in circulation, functions as a carrier protein, osmoregulator, and antioxidant. Generally, SA exerts its antioxidative effects by scavenging reactive oxygen species. Because marine mammals are superior divers, they are intermittently exposed to oxidative stress induced by rapid reperfusion of oxygen to ischemic tissues after the dive. Although several antioxidants in marine mammals have been described, SA activity remains largely uncharacterized. In this study, we investigated the antioxidative activity of SA in marine mammals by comparing features of the primary and steric structures, biochemical properties, and antioxidative activities of common bottlenose dolphin SA (DSA) and human SA (HSA). Our results revealed that DSA lacked free cysteine at position 34 that is important for the antioxidative activity of HSA; however, the antioxidative capacity and thiol activity of DSA were stronger than those of HSA. Circular dichroism spectra showed different patterns in DSA and HSA. Ultraviolet fluorescence intensities of DSA were higher than those of HSA, suggesting lower surface hydrophobicity of DSA. Additionally, DSA showed higher excess heat capacity than HSA. We then compared a homology model of DSA with a 3D model of HSA. Our results indicate that DSA was more unstable than HSA, probably due to the mode of molecules involved in the disulfide bonds and/or the lower surface hydrophobicity, and it may be related to the equivalent or stronger antioxidant potency of DSA. Our data show that DSA is not only an antioxidant but also a more unstable protein than HSA in the circulation at lease in the body-temperature range.